2021
DOI: 10.3389/fpubh.2020.560606
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Knowledge, Attitude, and Practice (KAP) of Nursing Staff and Influencing Factors on COVID-19

Abstract: The aim of this study is to investigate the knowledge, attitude, and practice (KAP) on Coronavirus Disease 2019 (COVID-19) care among nursing staff and analyze its influencing factors. The survey was conducted on February 18, 2020, among 7,716 voluntary participants from 143 medical institutions in Zhejiang, China. The findings indicated that KAP of nursing staff scored well. However, the accuracy of psychological nursing knowledge was much lower, 14.3% only. Nursing staff working in isolation wards have highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 8 publications
4
25
0
Order By: Relevance
“…Nurses who worked 3 years or more have a signi cantly higher score. This is in concordance with previous studies by Khan et al 25 , Hou et al 26 , and Wen et al 27 showing that working experience is associated with KAP scores. The higher the number of years working as a staff nurse, the more knowledgeable and con dent the healthcare worker is in dealing with public health emergencies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nurses who worked 3 years or more have a signi cantly higher score. This is in concordance with previous studies by Khan et al 25 , Hou et al 26 , and Wen et al 27 showing that working experience is associated with KAP scores. The higher the number of years working as a staff nurse, the more knowledgeable and con dent the healthcare worker is in dealing with public health emergencies.…”
Section: Discussionsupporting
confidence: 93%
“…The higher the number of years working as a staff nurse, the more knowledgeable and con dent the healthcare worker is in dealing with public health emergencies. [25][26][27] Patient outcomes and COVID 19 infection control and prevention is directly associated with the knowledge of nurses about the COVID-19 pandemic. 28 Scarcity of knowledge about this infectious disease escalates the risk of contagion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our further exploration of the data indicated that the HCWs' profession, education level, the nature of the working institution, and the number of prescriptions involved per week had an association with the attitude levels towards regulation of pharmaceutical promotion. Also, similar to knowledge levels, the variables associated with attitude levels are consistent with results from previous studies that have assessed factors associated with the attitude levels towards general medical practices [31,32]. Also, the results obtained from this study shows that most of the HCWs in Zimbabwe have high positive perceptions towards regulation of pharmaceutical promotion (i.e.90% had RII > 65%).…”
Section: Discussionsupporting
confidence: 89%
“…Our further exploration of the data indicated that the healthcare practitioners' profession, gender, education level, and the nature of the working institution had an association with the perception towards regulation of pharmaceutical regulation. Also, similar to knowledge and attitude levels, the variables associated with perception levels are consistent with results from previous that have assessed factors associated with the attitude levels towards general medical practices [31,32].…”
Section: Discussionsupporting
confidence: 87%